Preparation of flame retardant plastic using fine non-halogen materials (Journal of the College of Basic Education, 2022)
Environmentally friendly inorganic additives were used to inhibit the flammability and increase the ignition resistance of polypropylene. (Magnesium hydroxide) (Mg(OH)2) and (Mg(OH)2) were used with (SiO2) (Fumed Silica) to study the effect of The synergistic effect of these two compounds on flame resistance, and the success of these two compounds has been tested by approved and standard methods to show the efficiency of the additives in blocking flammability and approved by the American Society for Testing and Materials (ASTM). Through the results, it was found that the best percentage of magnesium hydroxide (Mg(OH) (2) It is (50%) the most effective in inhibiting the flammability and increasing the ignition resistance of polypropylene, and that the synergistic action of foamed silica with magnesium hydroxide gave the best result when using (8%, 5%) of foamed silica (SiO2) with (Mg) Oh)2)